Risk factors for poor prognosis in nosocomial infective endocarditis - Hwang, Ji-won (Korean J Intern Med, 2018)
BACKGROUND/AIMS: The aim of our study was to compare the characteristics of nosocomial infective endocarditis (NIE) with community-acquired infective endocarditis (CIE) and to determine independent risk factors for in-hospital death. METHODS: We retrospectively reviewed the medical records of 560 patients diagnosed with infective endocarditis. NIE was defined by a diagnosis made > 72 hours after hospital admission or within 2 months of hospital discharge. RESULTS: Among the 560 cases reviewed, 121 were classified as NIE. Compared with patients with CIE, patients with NIE were older (mean ± SD, 51.30±18.01 vs. 59.76±14.87, p < 0.001). The in-hospital death rate of the NIE group was much higher than that of the CIE group (27.3% vs. 5.9%, p < 0.001). More patients with NIE had central intravenous catheters, and were undergoing hemodialysis (p < 0.001). Methicillin-resistant Staphylococcus aureus (MRSA) was the most common causal microorganism of NIE, and MRSA (p < 0.001) and fungus (p = 0.002) were more common in NIE compared with CIE. On multiple analysis, age, liver cirrhosis, cancer chemotherapy, central intravenous catheter, hemodialysis, and genitourinary tract manipulation were independent clinical risk factors for NIE. Among the patients with NIE, 33 died during their hospital admission. The independent risk factors for in-hospital death were older age (adjusted odds ratio [OR], 1.04; 95% confidence interval [CI], 1.01 to 1.07; p = 0.037) and chemotherapy for malignancy (adjusted OR, 3.89; 95% CI, 1.18 to 12.87; p = 0.026). CONCLUSIONS: Because of the considerable incidence of NIE and its poor prognosis, we should pay attention to early diagnosis and active management of NIE, especially for older patients and patients receiving chemotherapy.